2015
DOI: 10.1515/jpm-2014-0356
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sonoelastography for improving prediction of preterm birth compared with cervical length measurement and fetal fibronectin test

Abstract: Cervical sonoelastography is a promising technique that can complement routine diagnostic procedures to improve prediction of preterm birth. The PPV is improved by an fFN test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Nowadays, sonoelastography is used to visualize tissue stiffness and elasticity by superimposing a colorcoded image, which is similar to color Doppler imaging. Cervical sonoelastography has been widely employed to evaluate cervical lesions [15] and preterm birth [18], or prior to the induction of labor [16]. However, while some authors have reported advantageous findings [33], others have found contradictory results [34].…”
Section: Discussion ▼mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, sonoelastography is used to visualize tissue stiffness and elasticity by superimposing a colorcoded image, which is similar to color Doppler imaging. Cervical sonoelastography has been widely employed to evaluate cervical lesions [15] and preterm birth [18], or prior to the induction of labor [16]. However, while some authors have reported advantageous findings [33], others have found contradictory results [34].…”
Section: Discussion ▼mentioning
confidence: 99%
“…Therefore, we chose to measure the tissue stiffness in the anterior cervical lip and internal os. Our method was described in previous studies of our group [15,18]. We investigated a moment not a time interval.…”
Section: Discussion ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements including cervical length via transvaginal ultrasonography, evaluation of the cervical tissue stiffness by sonoelastography and mean gray analysis were performed using quantitative ultrasound. The methods of detection and evaluation were determined by previous protocols 22 , 24 , 28 . Cervical length was defined as the distance between the internal and external os, which was measured in a sagittal plane of the cervix.…”
Section: Methodsmentioning
confidence: 99%
“…In the same issue, von Schöning and colleagues conducted a small prospective cohort study among 64 patients with preterm labor at 23-34 weeks to determine whether cervical sonoelastography improved prediction of PTB compared with CL measurement and fFN [14]. The former is a measure of cervical elasticity and consists of the ratio of nondeformable cervical tissue to the total region of interest.…”
mentioning
confidence: 99%